2007
DOI: 10.1007/s11340-006-9027-3
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Wiper System Dynamic Instabilities: Modelling and Experimental Validation

Abstract: The optimization of wiper systems under various conditions and the creation of a product which is as robust as possible are the main objectives for an equipment supplier. However, in certain conditions, instabilities can appear and generate wiping defects due to the rubber-glass contact. To improve wiping quality and to reduce the number of test stages for design, this study proposes a wiper system modeling method. The wiper system is represented by a rigid blade holder on which a rubber blade is fitted. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 8 publications
(8 reference statements)
0
25
0
Order By: Relevance
“…This sensitivity seems in changes of stability properties and thus in the amplitude of the self friction-induced vibrations. Moreover, it has been demonstrated that the friction coefficient admits strong dispersions [20,21]. Thus it is also necessary to take account of the uncertainty of the friction coefficient in order to ensure the robustness of the stability analysis and the prediction of self friction-induced vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…This sensitivity seems in changes of stability properties and thus in the amplitude of the self friction-induced vibrations. Moreover, it has been demonstrated that the friction coefficient admits strong dispersions [20,21]. Thus it is also necessary to take account of the uncertainty of the friction coefficient in order to ensure the robustness of the stability analysis and the prediction of self friction-induced vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…The non-linear static solution corresponds to the origin of the system (26). So, the eigenvalues  of the linearized system can be found by solving the characteristic equation:…”
Section: Parametric Study Of Stabilitymentioning
confidence: 99%
“…This confirms the improvement of the accuracy given by the non-intrusive methods. Fig.12 In a previous step, polynomial chaos was used intrusively and non-intrusively to estimate the first and second order statistics of the dynamic behaviour of the friction system (26) …”
Section: Non-intrusive Approachmentioning
confidence: 99%
“…In carrying out CEA, the computational model is usually considered as deterministic, and the fixed friction coefficient is applied. However, the friction coefficient is known to have strong dispersion characteristics depending on the operation conditions [7], and should be modeled as a random parameter. In addition, most physical systems are subject to uncertainties concerning the input parameters, such as the material properties and geometry, and the contact conditions.…”
Section: Introductionmentioning
confidence: 99%